Evaluation of Waiting Time and Transport Costs with Simulation in Urban Bus Transport - Emine Rumeysa KOCAER; Halil KORUCA; Samia CHEHBI-GAMOURA (International Journal of Applied Methods in Electronics and Computers, 2019)
It is important for both the bus owner and the passengers to determine the bus and minibus routes that are frequently used in urban passenger transport. Because the distance between the stops, the streets where the vehicle passes, the distance to reach the bus stop of passengers, how many minutes the bus will move, the waiting and transport time effects. Bus routes surround the entire residential area of the city as a network in various ways. The use of buses as a means of public transportation is preferred because it requires fewer infrastructure investments. The distance between stops, the population of settlements, the size/capacity of the bus and how many minutes the bus will move, determines the waiting time of passengers at the stop and duration of the tour. In this study, it is aimed to reduce bus operating costs and waiting times of passengers. Bus stops between Isparta center and Süleyman Demirel University West Campus, number and density of passengers, bus departure times and bus capacities were analyzed and modeled in the simulation software. As an alternative improvement scenario, buses with little and very passenger capacity were used and departure times were arranged. The effect of alternative scenarios on operating costs and waiting time was evaluated with the results obtained from simulation software.